The relationship between flexibility and agility to dribbling skills in adolescent football players: A correlational study - Muhammad Zulham Firmansyah; Fajar Awang Irawan; Adi S (Sriwijaya Journal of Sport, 2026)
Research Problems: This study focuses on the existing paucity of knowledge on the physical elements, specifically agility and flexibility, that contribute to teenage football players' dribbling skills. This is a crucial problem to examine, since dribbling is a fundamental technical skill that significantly affects how players perform in dynamic game situations. Research Objectives: This study aims to explore the relationship between the dribbling abilities of U17 players at the Darul Amanah Football Academy and flexibility and agility, both separately and in combination. Methods: 30 athletes were selected via total sampling as part of the study's quantitative correlational design. Flexibility, agility, and dribbling skill tests were used to gather data. Descriptive statistics, prerequisite tests (normality, linearity, and multicollinearity), product-moment correlation, and multiple regression analyses were used for analysis. Results: The study's findings show that while agility has a significant association with a somewhat negative correlation (r = -0,586; p < 0,05), flexibility has no significant partial relationship with dribbling skills (r = 0,143; p > 0,05). Dribbling skills are strongly influenced by both flexibility and agility at the same time (R = 0,587; R² = 0,344), suggesting a dual, albeit non-dominant, effect. Conclusion: In summary, flexibility is a supporting factor, while agility is the main factor affecting dribbling skills. These results highlight the value of agility-based training for young athletes' development and offer coaches useful advice for creating training plans. Future studies should look at other elements like coordination, balance, and cognitive features to create a more complete model.